A Morphable Ionic Electrode Based on Thermogel for Non‐Invasive Hairy Plant Electrophysiology. Issue 14 (4th March 2021) - Luo, Yifei; Li, Wenlong; Lin, Qianyu; Zhang, Feilong; He, Ke; Yang, Dapeng; Loh, Xian Jun; Chen, Xiaodong
Abstract: Plant electrophysiology lays the foundation for smart plant interrogation and intervention. However, plant trichomes with hair‐like morphologies present topographical features that challenge stable and high‐fidelity non‐invasive electrophysiology, due to the inadequate dynamic shape adaptability of conventional electrodes. Here, this issue is overcome using a morphable ionic electrode based on a thermogel, which gradually transforms from a viscous liquid to a viscoelastic gel. This transformation enables the morphable electrode to lock into the abrupt hairy surface irregularities and establish a conformal and adhesive interface. It achieves down to one tenth of the impedance and 4–5 times the adhesive strengths of conventional hydrogel electrodes on hairy leaves. As a result of the improved electrical and mechanical robustness, the morphable electrode can record more than one order of magnitude higher signal‐to‐noise ratio on hairy plants and maintains high‐fidelity recording despite plant movements, achieving superior performance to conventional hydrogel electrodes. The reported morphable electrode is a promising tool for hairy plant electrophysiology and may be applied to diversely textured plants for advanced sensing and modulation. Abstract : The complex surface topography on biological tissues presents a major challenge in bio‐electronic interfacing. Taking hairy plants as an example, an ionic electrode based on a thermogel is reported, which adapts and adheres to the abrupt hairy surface asperities, establishing a conformal and adhesive interface. It enables non‐invasive plant electrophysiological measurement with a signal fidelity not achievable by conventional gel electrodes.